Lao PDR - Investment Climate Assessment : Policies to Promote Growth in the Non-Resource Sectors - World Bank (World Bank, 2012)
The second Lao PDR investment climate assessment identifies the key constraints of the country's non-resource sector firms. This Assessment summarizes the results of a national survey conducted in late-2009 and draws on extensive interviews with policymakers and practitioners. Survey results reveal the nature of constraints that various non-resource sector firms in Lao PDR currently face. The results provide an analysis of the firms' performance and productivity. Supporting an international exchange of knowledge, this survey's results have been compared to numerous studies conducted by the World Bank in over 100 developing countries, which share similar methodological approaches. Due to rapid economic growth in recent years, Lao PDR has emerged from low income to middle-income country status in 2011, according to the World Bank. The development of the non-resource sector is essential to ensure sustainable and inclusive growth in Lao PDR. Non-resource sectors are more stable than resource sectors, and provide more long-term employment. The non resource sector is expected to contribute more than half of Lao PDR's real Gross Domestic Product (GDP) growth and 75 percent of the GDP in the medium-term. To achieve these results, policies in Lao PDR should focus on creating a positive enabling environment and that supports the development of the non-resource sectors. Based on Lao PDR's per capita income, this assessment's survey analysis demonstrates that labor productivity is lower than in neighboring countries and lower than in countries with a similar level of income. Labor productivity in Lao PDR is slightly lower than in Cambodia and Vietnam and significantly lags behind the leading countries in the region such as China, Malaysia and Thailand. Even though labor costs are low in Lao PDR, data suggests that national unit labor costs are roughly comparable to many comparator countries, but are higher than in China and Thailand.